Performance appraisal of the traffic intersection complex at Mokola, Ibadan, Nigeria - O.J. Oyedepo; L Ogunwolu; L Akinfala (Journal of Applied Sciences and Environmental Management, 2019)
Throughput time reduction is an integral part of transportation benefit analysis and traffic engineering optimization objectives. It is for this reason, that a large majority of transportation projects view throughput time reduction as one of their principal objectives. An appraisal of the performance of a traffic intersection complex at Mokola, Ibadan, Nigeria using a conflict intensity approach is presented. This work was carried out in order to quantify the effects of the flyover on the reduction of throughput times of vehicular traffic at the intersection. Conflict intensities were measured through traffic volume counts at various conflict points (through, merging and diverging locations). A floating vehicle equipped with a GPS was adopted to capture throughput times through several trial runs at the intersection. Statistical relationships were established between conflict intensities and throughput times using regression analysis. These relationships served as a framework for simulation for generating travel times (augmented), assuming the absence of a flyover. The results show a statistically significant reduction in throughput times due to the presence of the flyover with p-value of < 0.0001 at alpha level of 0.05 using Wilcoxon-Signed rank test. Specifically, reductions of 40.2seconds (33%) for northbound traffic and 27.6 seconds (28.8%) for southbound traffic were observed. This work has shown that the flyover reduced throughput times. The construction of the flyover is therefore justified and its residual potentials are enormous to handle traffic growth in the area in the near future.